Therapeutic potential of a rhein-loaded self-nano-emulsifying drug delivery system in ameliorating LPS-induced depression: mechanistic insights and behavioral outcomes - More, Sachin; Rashid, Md Abdur; Tiwari, Prashant Kumar; Kharwade, Rohini; Alhamhoom, Yahya; Asar, Turky Omar; Kaleem, Mohammed; Mahajan, Nilesh; Pise, Ajay; Danao, Kishor; Kumar, Sanjay (Frontiers in Pharmacology, 2025)
Depression is a multifaceted disorder caused by neuroinflammation, which is mainly demarcated by a significant increase in proinflammatory cytokines, including interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). Conventional treatments for depression typically focus on neurotransmitter theories and may lead to several undesirable side effects. Therefore, it is essential to identify innovative active compounds of herbal origin that can target proinflammatory cytokines to reduce neuroinflammation while minimizing side effects. Rhein has demonstrated considerable therapeutic efficacy in various neurological conditions; however, its mechanistic insights regarding antidepressant effects remain unclear. An in silico study of rhein against the putative target enzyme of depression showed prominent binding with neuroinflammatory proteins 1ALU, 2AZ5, and 5R88, achieving docking scores −5.84 kcal/mol, −5.23 kcal/mol, and −5.243 kcal/mol, respectively. However, the poor absorption of rhein limited its therapeutic efficacy. To address this issue, a rhein-loaded self-nano-emulsifying drug delivery system (R-SNEDDS) was developed and evaluated for its therapeutic effects in preventing a lipopolysaccharide-induced depression model in rats. The study found that intraperitoneal administration of R-SNEDDS (at doses of 50 mg/kg and 100 mg/kg rhein, i.p.) and duloxetine (as a positive control at 20 mg/kg) over three consecutive days reversed unusual depressive behaviors. Notably, the R-SNEDDS (100 mg/kg rhein, i.p.) significantly reduced levels of the proinflammatory cytokines IL-1β (30.91 ± 0.906), IL-6 (133.9 ± 2.232), and TNF-α (26.93 ± 1.807) compared to the lipopolysaccharide-induced group. These findings demonstrate that R-SNEDDS possesses anti-neuroinflammatory properties and could be promising for depression therapy.